Increased NOX2 expression in astrocytes leads to eNOS uncoupling through dihydrofolate reductase in endothelial cells after subarachnoid hemorrhage - Miao, Shu-Hao; Gao, Sheng-Qing; Li, Hui-Xin; Zhuang, Yun-Song; Wang, Xue; Li, Tao; Gao, Chao-Chao; Han, Yan-Ling; Qiu, Jia-Yin; Zhou, Meng-Liang (Frontiers in Molecular Neuroscience, 2023)
Endothelial nitric oxide synthase (eNOS) uncoupling plays a significant role in acute vasoconstriction during early brain injury (EBI) after subarachnoid hemorrhage (SAH). Astrocytes in the neurovascular unit extend their foot processes around endothelia. In our study, we tested the hypothesis that increased nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX2) expression in astrocytes after SAH leads to eNOS uncoupling. We utilized laser speckle contrast imaging for monitoring cortical blood flow changes in mice, nitric oxide (NO) kits to measure the level of NO, and a co-culture system to study the effect of astrocytes on endothelial cells. Moreover, the protein levels were assessed by western blot and immunofluorescence staining. We used CCK-8 to measure the viability of astrocytes and endothelial cells, and we used the H2O2 kit to measure the H2O2 released from astrocytes. We used GSK2795039 as an inhibitor of NOX2, whereas lentivirus and adeno-associated virus were used for dihydrofolate reductase (DHFR) knockdown in vivo and in vitro. The expression of NOX2 and the release of H2O2 in astrocytes are increased, which was accompanied by a decrease in endothelial DHFR 12 h after SAH. Moreover, the eNOS monomer/dimer ratio increased, leading to a decrease in NO and acute cerebral ischemia. All of the above were significantly alleviated after the administration of GSK2795039. However, after knocking down DHFR both in vivo and in vitro, the protective effect of GSK2795039 was greatly reversed. The increased level of NOX2 in astrocytes contributes to decreased DHFR in endothelial cells, thus aggravating eNOS uncoupling, which is an essential mechanism underlying acute vasoconstriction after SAH.